DIAGNOSTIC VALUE OF URINARY BIOMARKERS IN CHRONIC KIDNEY DISEASES AT CHILDREN - Jordanova, Olivera; Tasic, Velibor; Sofijanova, Aspazija; Cekovska, Svetlana; Bojadzieva, Sonja; Abazi, Nora; Nonkulovski, Danilo; Janchevska, Aleksandra; Teov, Bojan; Torkovska, Marija; Bekjiri Jasari, Ardiana (Journal of Morphological Sciences, 2023)
Chronic kidney disease(CKD) typically develops as a consequence of gradually advancing kidney ailments, and it rarely sees complete reversibility. The aim of the study is to evaluate the value of urinary biomarkers in children with progression of chronic kidney disease. The  is a retrospective-prospective study in which includes 95 pediatric patients with clinical signs, symptoms, laboratory analyses, and imaging studies for CKD. The patients are aged 0 to 14 years who came to the University Clinic for Children's Diseases-Skopje at the nephrology department and the subspecialist nephrology outpatient clinic, in period from January 2019 to June 2022. The study group is divided into three groups, study group 1, which includes 41/95 pediatric patients(43.16%)with congenital anomalies of the kidneys and urinary tract, study group 2, which includes 34/95 pediatric patients(35.79%)with tubulopathies and metabolic disorders with renal affection and study group three which includes20/95(21.05%)pediatric patients with other nephrological-urological diseases. In our study, CKD is more prevalent in males 64 (67.37%) while 31 (32.63%) are females, according to age, patients aged 5-14 years (57.3 %). The average values of urine NGAL(ng/ml), Î²2-Microglobulin and albuminirua showed that there is a significant difference in relation to this parameter in three groups of pediatric patients at the first examination (p<0.05). As the landscape of CKD continues to reveal novel insights into its intricate mechanisms, urine biomarkers will continue to assume a pivotal role in furthering our comprehension of the disease and shaping the trajectory of personalized medicine for CKD children. Keywords: chronic kidney disease (CKD), urine biomarkers, NGAL (Neutrophil Gelatinase Associated Lipocalin.